Optimizing Educational Data Management for Evidence-Based Decision Making in Educational Institutions in the Society 5.0 Era - Hernawati W Retno Wiratih; Bruno Rumyaru; Hazimi Bimaruci Hazrati Havidz (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the persistent problem of data fragmentation that prevents educational institutions from fully implementing evidence-based decision making within the Society 5.0 era. The research aims to analyze how unintegrated data systems hinder institutional responsiveness and to identify strategic solutions for optimizing educational data management. Using a library research method, data were collected from books, scientific articles, reports, and prior studies related to educational data optimization, learning analytics, and institutional digital transformation. The analysis shows that fragmented data limits the accuracy of decisions, restricts the use of advanced analytics, and contradicts the human-centered technological vision of Society 5.0. The study concludes that integrated and interoperable data systems are essential for strengthening decision-making processes, improving educational quality, and enabling effective digital innovation in educational institutions.